A new method for extraction of alteration information using the Landsat 8 imagery in a heavily vegetated and sediments‐covered region: A case study from Zhejiang Province, E. China. (9th August 2017) - Han, Ling; Zhao, Bo; Wu, Jian‐jian; Wu, Ting‐ting; Feng, Min
Abstract : Ore prediction based on the Operational Land Imager (ETM + ) image within the heavily vegetated and sediments‐covered areas is always a difficulty for geological remote sensing. Here, we report a new scheme for extraction of near‐ore alteration information in such localities: Terrain Analysis → principal component analysis →Fractal → Spatial Overlay and the Fe 3+ –OH − integrated anomalies that are punctate and probably ore‐caused were reasonably exposed. Findings showed a satisfactory result that the spatial, if not genetic, dependency relationship between the remotely sensed anomalies and geochemical anomalies, as well as the ore‐controlling geological bodies, is significant. However, no substantial spectral anomalies of vegetation immediately responsible for local mineralization and alteration were detected. This study may have contributed a useful case study for in‐depth remote sensing exploration.